Light energy transduction in liposome-based artificial cells - Albanese, Paola; Mavelli, Fabio; Altamura, Emiliano (Frontiers in Bioengineering and Biotechnology, 2023)
In this work we review the latest strategies for the bottom-up assembly of energetically autonomous artificial cells capable of transducing light energy into chemical energy and support internalized metabolic pathways. Such entities are built by taking inspiration from the photosynthetic machineries found in nature which are purified and reconstituted directly in membrane of the artificial compartment or encapsulated in form of organelle-like structures. Specifically, we report and discuss recent examples based on liposome-technology and multi-compartment (nested) architectures pointing out the importance of this matter for the artificial cell synthesis research field and some limitations and perspectives of the bottom-up approach.